ANALISIS POLA PENGOBATAN HIPERTENSI TERHADAP TEKANAN DARAH PASIEN RAWAT INAP GERIATRI DI RUMAH SAKIT X GUMAWANG 2024 - Widya Puspita Sari; Eva Nurinda; Sri Suprapti; Ari Susiana Wulandari (Universitas Ubudiyah Indonesia, 2026)
Hypertension in the elderly has a high prevalence and poses a risk of serious complications such as stroke and heart disease. Optimal blood pressure control is crucial, but it is often hindered by the inappropriate selection of antihypertensive medications. This study analyzed the patterns of antihypertensive treatment and their effects on blood pressure among geriatric inpatients at X Hospital Gumawang in 2024. Using a retrospective design with purposive sampling of 98 patients, data were obtained from medical records and analyzed using the Chi-Square test. The results showed that most patients received a combination of two antihypertensive drugs (41.8%) and achieved controlled blood pressure (66.3%) after therapy. The Chi-Square test indicated a significant relationship between treatment patterns and blood pressure (p=0.042), suggesting that appropriate antihypertensive therapy selection influences blood pressure control in the elderly.